An Effective Additive for Introducing the Triazole Unit of Ensitrelvir: Combination of LiCl and Et3N to Easily Generate Lithium Triazinolate - Ohashi, Eisaku; Sahara, Naoto; Hirano, Yoichi; Hosoya, Masahiro; Takahashi, Yusaku; Tsuno, Naoki (Synthesis, 2023)
An efficient and robust method was developed to introduce the triazole unit of Ensitrelvir, a COVID-19 therapeutic agent. One of the key steps is introducing the triazole unit in the triazinone with Cs2CO3 and KI in a heterogeneous system. Detailed reaction screening revealed that addition of LiCl allowed the reaction to proceed quantitatively in the presence of inexpensive Et3N, and the selectivity of the N-alkylation was greatly improved. The key to promoting the reaction is the mild formation of the lithium triazinolate accompanied by precipitation of Et3N·HCl (the only insoluble matter in this reaction). Dissolving all the substrates and reagents should contribute to further improvement of the process robustness.
Keywords: Ensitrelvir; triazole; N-alkylation; triazinone; LiCl; organic base; lithium triazinolate; precipitation